Pharmacodynamic Monitoring of Mycophenolic Acid Therapy: Improved Liquid Chromatography–Tandem Mass Spectrometry Method for Measuring Inosin-5′-Monophosphate Dehydrogenase Activity. Issue 2 (April 2020) - Weißbarth, Gero; Wiesen, Martin H. J.; Fietz, Cornelia; Streichert, Thomas; Ehren, Rasmus; Weber, Lutz T.; Müller, Carsten
Abstract : Background: Mycophenolic acid (MPA), a powerful inhibitor of lymphocyte proliferation, is widely used in transplantation medicine and as a glucocorticoid-sparing agent in rheumatic and inflammatory diseases. As inosine-5′-monophosphate dehydrogenase (IMPDH), the target enzyme of MPA, shows high interindividual variability in its basal activity, the assessment of IMPDH activity in addition to pharmacokinetic monitoring has emerged as a strategy to individualize MPA pharmacotherapy. Methods: A liquid chromatography–tandem mass spectrometry method was developed to measure IMPDH activity in peripheral blood mononuclear cells from lithium-heparinized blood. Stable isotope-labeled analogs of analytes were used as internal standards for the quantitative analyses of xanthosine-5′-monophosphate (XMP) and adenosine-5′-monophosphate (AMP). IMPDH activity was expressed as enzymatic production of XMP per time normalized to the AMP concentration. Validation and evaluation of the new method were performed by using blood samples from healthy volunteers (n = 10). Results: Linearity was demonstrated over the concentration ranges of 0.25–80 μM for XMP and 4–80 µM for AMP (R 2 > 0.99). Between-day and within-day assay precisions and accuracies were within the acceptance criterion of ±15%. Matrix effects were fully compensated by the coelution of internal standards. Specific and linear XMP production (R 2 > 0.99) and the inhibition of IMPDH activity by MPA at clinically relevant doses were demonstrated. Conclusions: In this study, a liquid chromatography–tandem mass spectrometry method to measure IMPDH activity was established and fully evaluated for matrix and ion suppression effects. The method enabled precise quantification of IMPDH activity for the improvement of pharmacokinetic/pharmacodynamic therapeutic drug monitoring approaches to optimize immunosuppressive treatment with MPA. Abstract : Supplemental Digital Content is Available in the Text.